(untitled) (Journal of the Spanish Institute for Strategic Studies, 2018)
Th is paper looks at the complicated situation that mexico has been facing since the beginning of the national public security system reform process in 2006. Th e decision to reform mexican security institutions had been delayed. when the country decided to face up to this challenge, both organized crime and the structural failings of the security agencies forced the government to take on a double challenge: to recover ungovernable territories infi ltrated by organized crime – for which the state will need to fall back on the armed forces, and to fully restructure the national public security system. Th is paper shows that the argument that mexico doesn’t invest enough resources in public security is not in line with reality, but rather that precisely federal and municipal entities have invested the most. Th is argument that is in stark contrast to the scarce results that are to be seen forces society to take a concerned look at the destination and use of public resources and highlights the importance of the debate on the police «single command» in mexican federal entities.